1997
DOI: 10.1109/10.641330
|View full text |Cite
|
Sign up to set email alerts
|

Early recognition of postural disorders in multiple sclerosis through movement analysis: a modeling study

Abstract: In the present study, spontaneous postural behavior has been analyzed in freely standing multiple sclerosis (MS) patients, exhibiting no clinically assessable abnormalities of postural control. This population has been compared with two other groups, healthy people and hemiparetic patients. This latter group represents a situation where the central nervous system (CNS) lesion is precisely localized in one anatomical site and no signal-conduction disorders are present; i.e., it has an opposite anatomical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 24 publications
3
49
0
Order By: Relevance
“…These tests are partly based on subjective ratings and provide no guarantee that there is no balance problem when the assessment is negative. There are MS patients who complain about subjective discomfort of balance even if there is no clinical evidence of any balance problem [1]. Detecting minimal impairment of balance based on observation is not easy as confirmed by our neurologists who examined the videos.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These tests are partly based on subjective ratings and provide no guarantee that there is no balance problem when the assessment is negative. There are MS patients who complain about subjective discomfort of balance even if there is no clinical evidence of any balance problem [1]. Detecting minimal impairment of balance based on observation is not easy as confirmed by our neurologists who examined the videos.…”
Section: Discussionmentioning
confidence: 85%
“…In multiple sclerosis (MS) patients detection of balance deficits is challenging because MS patients often complain about balance problems when the Romberg test is negative and gait tests are normal [1]. Other clinical tests, for example, the Berg Balance Scale and Tinetti Performance Oriented Mobility Assessment, are also not sensitive enough to detect minimal balance impairment in MS patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique would provide objective measures of interventional changes rather than the current methods of self-report or distantly related outcomes such as walking, mobility, or balance. Furthermore, previous studies have shown the challenges of diagnosing balance impairments in patients with MS [37][38]. These studies demonstrated the limitations of current methods, such as biomechanical analysis with force platforms and EMG, to identify balance impairments in patients with MS.…”
Section: Discussionmentioning
confidence: 78%
“…Regarding stabilometric data analysis, body sway parameters have been used for analysis balance-related functions [8], [9]. However, it appears that classic posturographic parameters, such as the measure of the sway of the centre of pressure [10] have failed in the detection of balance disorders [11]. The analysis of stabilometric time series using data mining techniques offers new possibilities.…”
Section: Fig 1 Patient Completing a Test On A Posturographmentioning
confidence: 99%